RETRACTED : The Effect of Financial Compensation, Work Motivation and Work Discipline on The Performance of Permanent Employees of PT Outsource Indonesia - Novia Santi; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science, 2024)
This research aims to analyze how much influence Financial Compensation, Work Motivation and Work Discipline on employee performance. In this research using primary data obtained from questionnaires to 116 employees as respondents in companies jabbek. This research uses descriptive analysis and inferential analysis methods. Data were analyzed using multiple linear regression correlation analysis, test instruments, test the feasibility of the model, and the t test. The results of this study indicate a positive and significant effect on Employee Performance, which is generated from the results of the regression equation model in the Coefficients Y table = 5.653 + 0.508 + 0.082+ 0.234. In the model feasibility test results obtained significant value of 0,000 which means the model is said to be significant and the model is said to be feasible to use in this study. On the results of the t-test hypotheses obtained sig value on the variable Financial Compensation of 0,000, the sig value on the Work Motivation variable is 0.046, and the sig value in the Work Discipline is 0,000. Then it can be concluded that the partial meaning of the three variables has a positive and significant influence on the dependent variable of employee performance.